Frank Bettger's How I raised myself from failure to success in selling : a modern-day interpretation of a self-help classic - McCreadie, Karen (Petaling Jaya, Selangor : MPH Bookstore, 2010)
'Frank Bettger's momentous decision to undergo a complete personal transformation by putting enthusiasm into everything he did helped him achieve legendary status as an insurance salesman. His first book, published in 1947,'How I Raised Myself from Failure to Success' is still a best-seller today and has stood the test of time. Here, Karen McCreadie's interpretation of'How I Raised Myself from Failure to Success' illustrates the timeless nature of Bettger's insights by bringing them to life through 52 modern case studies. This brilliant interpretation of'How I Raised Myself from Failure to Success' is an entertaining accompaniment to one of the most famous books on selling ever written.'--Resource description page.
Includes bibliographical references (p. 116-117) and index.
Keywords: Bettger, Frank; Success in business; Selling; Selling -- Psychological aspects; Self-actualization (Psychology)